Optimization, Characterization, and Antibacterial Activity of Copper Nanoparticles Synthesized Using Senna didymobotrya Root Extract. (15th October 2021) - Sadia, Bernard Otieno; Cherutoi, Jackson Kiplagat; Achisa, Cleophas Mecha
Abstract : The economic burden and high mortality associated with multidrug-resistant bacteria is a major public health concern. Biosynthesized copper nanoparticles (CuNPs) could be a potential alternative to combat bacterial resistance to conventional medicine. This study for the first time aimed at optimizing the synthesis conditions (concentration of copper ions, temperature, and pH) to obtain the smallest size of CuNPs, characterizing and testing the antibacterial efficacy of CuNPs prepared from Senna didymobotrya ( S. didymobotrya ) roots. Extraction was done by the Soxhlet method using methanol as the solvent. Gas chromatography-mass spectrometry (GC-MS) analysis was performed to identify compounds in S. didymobotrya root extracts. Box–Behnken design was used to obtain optimal synthesis conditions as determined using a particle analyzer. Characterization was done using ultraviolet-visible (UV-Vis), particle size analyzer, X-ray diffraction, zeta potentiometer, and Fourier transform infrared (FT-IR). Bioassay was conducted using the Kirby–Bauer disk diffusion susceptibility test. The major compounds identified by GC-MS in reference to the NIST library were benzoic acid, thymol, N-benzyl-2-phenethylamine, benzaldehyde, vanillin, phenylacetic acid, and benzothiazole. UV-Vis spectrum showed a characteristic peak at 570 nm indicating the formation of CuNPs. The optimum synthesis conditions were temperature of 80°C, pH 3.0, and copper ion concentration of 0.0125 M. The FT-IR spectrum showed absorptions in the range 3500–3400 cm −1 (N-H stretch), 3400–2400 cm −1 (O-H stretch), and 988–830 cm −1 (C-H bend) and peak at 1612 cm −1 (C=C stretch), and 1271 cm −1 (C-O bend). Cu nanoparticle sizes were 5.55–63.60 nm. The zeta potential value was −69.4 mV indicating that they were stable. The biosynthesized nanoparticles exhibited significant antimicrobial activity on Escherichia coli and Staphylococcus aureus with the zone of inhibition diameters of 26.00 ± 0.58 mm and 30.00 ± 0.58 mm compared to amoxicillin clavulanate (standard) with inhibition diameters of 20 ± 0.58 mm and 28.00 ± 0.58 mm, respectively.